Pengaruh Disiplin Kerja, Lingkungan Kerja dan Komitmen Organisasi Terhadap Kinerja Karyawan (Studi pada Dinas Pemadam Kebakaran Kota Batu) - Amalia, Putri Hafida; Priyono, Achmad Agus; Slamet, Afi Rachmat (UNIVERSITAS ISLAM MALANG, 2025)
Abstract This research aims to analyze the influence of work discipline, work environment, and organizational commitment on employee performance at the Fire Department of Batu City. The approach used in this research is quantitative, with a population of 81 employees. The sampling technique was carried out using a non-probability sampling method, resulting in a sample of 43 employees with ASN (civil servant) status. Data analysis was carried out using multiple linear regression, with hypothesis testing through the F-test and t-test. The results show that work discipline has a significant effect on employee performance, while the work environment and organizational commitment do not have a significant influence. However, simultaneously, work discipline, work environment, and organizational commitment have been proven to significantly affect employee performance. Keywords: Work Discipline, Work Environment, Organizational Commitment